Immunity Of Foreign Embassies From Jurisdiction Of Indonesian Industrial Relations Court Of Indonesia (A Case Study of Decision Number 376 K/Pdt.Sus-Phi/2013) - Fahar Fatoni; Muh. Risnain; Diva Pitaloka (Mataram Journal of International Law, 2024)
This research aims to determine the position of foreign embassies within the jurisdiction of the Indonesian Industrial Relations Court under the 1961 Vienna Convention and the implementation of foreign embassies’ diplomatic immunity by the Industrial Relations Court in Decision Number 376 K/Pdt.Sus-PHI/2013. This research uses a normative research method, employing both an international agreement approach and a conceptual approach. Foreign embassies enjoy several broad immunities from the jurisdiction of the receiving country. Courts in Indonesia cannot necessarily hear or decide cases involving foreign embassies. A special agreement is needed that allows diplomatic agents to comply with applicable laws in Indonesia, and this must be submitted separately. Diplomatic representatives are parties who can be involved in industrial relations dispute cases at the Industrial Relations Court. Under the 1961 Vienna Convention, these immunities and privileges are not absolute, and the receiving country has the power to reject diplomatic representation considered problematic or persona non grata.